Answer:
Did you mean [tex]cos[/tex] instead of [tex]cis[/tex] ?
If that's the case, then the answer is:
[tex]3\sqrt{2} cos(\frac{\pi}{12})*2\sqrt{5} cos(\frac{4 \pi}{3}) =6\sqrt{10} cos(0.66043941112\pi) \approx -9.16[/tex]
Step-by-step explanation:
As you may know:
[tex]\sqrt{ab} =\sqrt{a}* \sqrt{b}[/tex]
So:
[tex]3\sqrt{2} *2\sqrt{5} =3*2*\sqrt{2*5} =6\sqrt{10}[/tex]
Now:
[tex]cos(\frac{\pi}{4}) =\frac{\sqrt{6} +\sqrt{2} }{4} \\\\and\\\\cos(\frac{4\pi}{3} )=-\frac{1}{2}[/tex]
So:
[tex]cos(\frac{\pi}{12} )*cos(\frac{4\pi}{3} )=(\frac{\sqrt{6}+\sqrt{2} }{4} )*(-\frac{1}{2} ) =\frac{-\sqrt{6}-\sqrt{2} }{8}[/tex]
Now, using the inverse cosine:
[tex]arccos(\frac{-\sqrt{6}-\sqrt{2} }{8})=2.074831602=0.66043941112\pi[/tex]
Therefore, the equivalent expression for the product of 3√2cis(π/12) and 2√5cis(4π/3) is:
[tex]3\sqrt{2} cos(\frac{\pi}{12})*2\sqrt{5} cos(\frac{4 \pi}{3}) =6\sqrt{10} cos(0.66043941112\pi) \approx -9.16[/tex]